2015
DOI: 10.1007/s00167-015-3863-6
|View full text |Cite
|
Sign up to set email alerts
|

Femur bowing could be a risk factor for implant flexion in conventional total knee arthroplasty and notching in navigated total knee arthroplasty

Abstract: Retrospective comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Recently, more and more surgeons have realized the significance of the femoral shape in the sagittal plane. Ko et al thought sFBA was a risk factor for femoral implant flexion in conventional intramedullary TKA and notching in navigated TKA [ 8 ]. Nakahara et al promoted an idea that sagittal femoral cutting error could change femoral anteroposterior sizing in TKA, for example, downsizing of the femoral component could occur if the distal osteotomy was performed in a flexed position [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more and more surgeons have realized the significance of the femoral shape in the sagittal plane. Ko et al thought sFBA was a risk factor for femoral implant flexion in conventional intramedullary TKA and notching in navigated TKA [ 8 ]. Nakahara et al promoted an idea that sagittal femoral cutting error could change femoral anteroposterior sizing in TKA, for example, downsizing of the femoral component could occur if the distal osteotomy was performed in a flexed position [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the recognized results in the coronal plane, there is no unified peri-operative alignment assessment system of femur in the sagittal plane. It has been shown sFBA is associated with the degree of femoral component flexion [ 8 ]. An overly flexional position will limit knee extension and result in posterior insert wear caused by impingement between the polyethylene insert and the intercondylar box in TKA using post-cam mechanism [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We should make an adequate bone bed for the anterior flange of the femoral component with proper cementing technique. Furthermore, caution should be taken to avoid anterior notching in knees with severe femoral anterior bowing, particularly when using computer assisted navigation [4,13,17]. Postoperative rehabilitation is also impo rtant.…”
mentioning
confidence: 99%
“…Neither the surgeons nor the implant manufacturers had a clear consensus on the direction and depth in using the intramedullary rod in TKA. The operation was often decided by the surgeon, based on the preoperative image data and intraoperative experience, so the accuracy of the sagittal position of the femoral component could not be ensured 20 . Earlier studies had demonstrated that using the conventional alignment technique a femoral flexion within the range from 0 to 5 flexion was achieved in only 25% and 48% of TKA, respectively.…”
Section: Sagittal Insertion Depth and Direction Of The Femoral Intrammentioning
confidence: 99%
“…Earlier studies had demonstrated that using the conventional alignment technique a femoral flexion within the range from 0 to 5 flexion was achieved in only 25% and 48% of TKA, respectively. 20,21 However, that study did not explore how to improve the accurate placement of the component. Up to now, no clinical or anatomical studies have explored this.…”
Section: Sagittal Insertion Depth and Direction Of The Femoral Intrammentioning
confidence: 99%